Behavioral Science is Wonderful to Be Sure: But is it Scientific, Too? - Samsa, Greg (Archives of Business Research, 2018)
Behavioral finance is touted as, among others, a scientific approach to investment which combines psychology and economics, and investigates the consequences in markets when some of its participants display not logically perfectly-informed risk-averse utility-maximizing behavior, but instead act like actual human beings. Two questions are considered: (1) “What does the science of behavioral finance imply about the behavior of stock prices?”; and also (2) “Are the predictions that behavioral makes about the behavior stock prices scientific?” This is a thought piece organized around these two questions. Using Popper’s framework that scientific hypotheses require falsifiability, we conclude that behavioral finance is only falsifiable (and thus “scientific”) in a limited sense.